FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN LAPORAN PERTANGGUNGJAWABAN TERHADAP KUALITAS LKPD - Karolina Dahay (Universitas Cenderawasih, 2020)
Systems, Information Technology, and Government Accounting Standards. The study used is qualitative and quantitative data. The research used quantitative data analysis: instruments test classical assumption test, and multiple regression analysis. The results show that Human Resources competency and the application of Government Accounting Standards have a significant effect on the quality of local government reports. In contrast, Internal Control System and Information Technology do not have a considerable impact. Together all factors have a significant effect on the quality of LKPDLocal Government Reports.